Transforaminal Epidural Steroid Injection Technique: Fluoroscopy-Guided Minimally Invasive Injection for Lower Limb Radiculopathy—Twelve Golden Steps - Mahesh Kumar; Sanjay Khanna; Dharmendra Kumar Singh; Nishith Kumar (Indian Journal of Radiology and Imaging)
Radicular back pain is defined as low back pain radiating into the lower extremities in a dermatomal pattern caused by compression or irritation of the nerve root. Fluoroscopy is an excellent tool for the management of lower limb radiculopathies that are secondary to discogenic pathologies not responding to the conservative trial. Transforaminal epidural steroid injection technique is a minimally invasive intervention for radiculopathies, which can easily be done in a day care setting, and it should be considered before surgery; however, precision and expertise is required.